2014
DOI: 10.3171/2014.6.spine13756
|View full text |Cite
|
Sign up to set email alerts
|

Nerve growth factor promotes expression of novel genes in intervertebral disc cells that regulate tissue degradation

Abstract: Object Increased neurotrophin activity in degenerative intervertebral discs (IVDs) is one potential cause of chronic low-back pain (LBP). The aim of the study was to assess if nerve growth factor (NGF) might alter gene expression of IVD cells and contribute to disc degeneration by enhancing expression or activity of factors that cause breakdown of IVD matrix. Methods Rat-tail IVD cells were stimulated by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 46 publications
0
18
0
Order By: Relevance
“…In this study, we have observed that NGF, which is likely to play a role in nerve ingrowth into the degenerated IVD [5,18], may also act as a catabolic factor promoting disc degeneration [15]. The observation that NGF induced overexpression of lipocalin 2 to enhance MMP9 activity in AF cells is previously unreported.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…In this study, we have observed that NGF, which is likely to play a role in nerve ingrowth into the degenerated IVD [5,18], may also act as a catabolic factor promoting disc degeneration [15]. The observation that NGF induced overexpression of lipocalin 2 to enhance MMP9 activity in AF cells is previously unreported.…”
Section: Discussionmentioning
confidence: 74%
“…The detailed microarray methods and results were provided in our previous study [15]. Briefly, gene expression analysis of rat-tail disc cells with or without NGF stimulation for 5 days was undertaken using the Rat Whole Genome OneArray TM (Phalanx Biotech Group, Hsinchu, Taiwan), signals being scanned by an Axon 4000 scanner (Molecular Devices, Sunnyvale, CA, USA).…”
Section: Microarray Assaymentioning
confidence: 99%
See 2 more Smart Citations
“…Increased neurotrophin activity is one potential cause of IDD. Nerve growth factor (NGF) stimulation has been shown to upregulate MMP-3 expression and increase the ratio of MMP-3 to tissue inhibitor of metalloproteinase (TIMP)-3 in rat and human IVD cells and tissue, which is abolished by Ro 08-2750, a specific inhibitor of NGF [65]. A later study by the same authors has demonstrated that NGF also augments the expression and activity of MMP-9 in rat AF cells by upregulating lipocalin 2 expression [66].…”
Section: Mmps and Iddmentioning
confidence: 99%